1996
DOI: 10.1038/384427a0
|View full text |Cite
|
Sign up to set email alerts
|

Endosome dynamics regulated by a Rho protein

Abstract: Vesicular transport is a dynamic process that requires coordinated interactions between membrane and cytoskeleton. The mechanisms and molecules integrating these interactions are unclear. A Rho protein, RhoD, might provide a molecular link between membrane traffic and the cytoskeleton. Activated RhoD causes rearrangements of the actin cytoskeleton and cell surface, and governs early endosome motility and distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
1
15

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(220 citation statements)
references
References 37 publications
10
194
1
15
Order By: Relevance
“…To determine the entire coding sequence of gMt1, we screened a C2 myotube cDNA library with the PCR product and obtained six positive clones (gMt1a ± f). Among them, gMt1e included an entire coding sequence, which was identical to recently reported RhoD (Murphy et al, 1996). gMt1d contained another sequence coding for a novel small GTPase.…”
Section: Cloning Of M-ras and Rhodmentioning
confidence: 68%
See 2 more Smart Citations
“…To determine the entire coding sequence of gMt1, we screened a C2 myotube cDNA library with the PCR product and obtained six positive clones (gMt1a ± f). Among them, gMt1e included an entire coding sequence, which was identical to recently reported RhoD (Murphy et al, 1996). gMt1d contained another sequence coding for a novel small GTPase.…”
Section: Cloning Of M-ras and Rhodmentioning
confidence: 68%
“…Thus, it is necessary to investigate the roles of M-Ras and RhoD, in addition to the other Ras and Rho family proteins, in the above cellular events during myogenesis. Particularly, since M-Ras, Cdc42, Rac1 and RhoD are likely to mediate reorganization and disappearance of the stress ®bers (Kozma et al, 1995;Murphy et al, 1996;Manser et al, 1997) (data not shown), they may hinder the development of the structurally related myo®lament bundles. Alternatively, because the stress ®bers are replaced by the myo®lament bundles during myo®brillogenesis, disassembly of the stress ®bers by these small GTPases may be a prerequisite for the formation of myo®lament bundles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the physical trafficking of endoplasmic reticulum towards the plasma membrane is another mechanism to be considered [3]. Recently, Rho D has been proposed as a candidate for a molecule that co-ordinates vesicle transport with the rearrangement of the actin cytoskeleton [64]. (3) The control of actin reorganization by Ras proteins [16,17,30,31] could participate in the maintenance of a cytoskeletal structure supporting a direct coupling between the intracellular stores and the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The RhoD GTPase is present at the plasma membrane and on early endocytic vesicles [70]. Expression of constitutively active RhoD causes alignment of these vesicles with actin filaments and a loss of early endocytic motility [70,71].…”
Section: Rhod and Early Endosomesmentioning
confidence: 99%